Grassroots to gold exploring the use of athletes' narrative through dynamic visual narrative approach in the production of promotional video for Palarong Pambansa 2019 - Arpon, Honey Rose C.; Pueblas, Mishael Jacob L. (2019)
Filipinos are known for being fond of sports. From grassroots to international level, there are lots of sports competition that the Filipinos can participate in. For one, Palarong Pambansa, as the largest national grassroots sports event in the country, has long been an avenue for the youth to participate in sports activities. However, with today?s advanced technology, the youth have become more inclined to a digital lifestyle that it affected their engagement in sports. According to the study conducted by DOST-FNRI (2008), Filipino youth?s participation in sports activities have declined to 7%. With this issue at hand, the sports industry ? specifically the Philippine Sports Commission ? recognizes the vital role of media to continuously promote sports to the youth. Thus, the researcher utilized the capability of media by producing a promotional video for Palarong Pambansa 2019. In creating the promotional video, the researcher utilized the narratives of the athletes through Dynamic Visual Narrative approach. As part of this study?s formative research, the researcher looked for Mindanawon young athletes who were eligible for Palarong Pambansa 2019 through purposive sampling and snowball method. A total of six athletes were engaged in an individual in-depth interview to better understand their narratives as athletes. After conducting a thematic analysis on the data gathered, the researcher was able to produce an episodic promotional video which consisted of six episodes that featured one athlete for each. The six episodes of the promotional video were uploaded in the official Facebook page of the University of the Philippines Mindanao and the entire material reached a total of 97,000 Facebook users.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019